Deglacial bottom water warming intensified Arctic methane seepage in the NW Barents Sea - Naima El bani Altuna (Nature Portfolio, 2021)
Phases of high bottom water temperature in the northwestern Barents Sea caused repeated destabilization of methane gas hydrates since the last glacial, according to a foraminifera Mg/Ca bottom water temperature record and hydrate stability modelling